PENINJAUAN SATELIT PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI SUMBER ENERGI LISTRIK ALTERNATIF - , RIZKY JANUAR, Ir. Bambang Sugiyantoro, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The rapid growth of world electricity demand and imminent scarcity of fossil energy reserve call for an alternative energy development. The perpetual availability of the sun yields the idea of solar power satellite. This thesis estimates the output power of two solar power satellite designs, SPS2000 and Sun Tower